Oncological outcomes of neoadjuvant chemotherapy in patients with resectable synchronous colorectal liver metastasis: A result from a propensity score matching study - Jiang, Yu-Juan; Zhou, Si-Cheng; Chen, Jing-Hua; Liang, Jian-Wei (Frontiers in Oncology, 2022)
Background The efficacy and safety of neoadjuvant chemotherapy (NAC) in treating resectable synchronous colorectal liver metastases (CRLM) remain controversial. Methods Data from CRLM patients who underwent simultaneous liver resection between January 2015 and December 2019 were collected from the Surveillance, Epidemiology, and End Results (SEER) database (SEER cohort, n=305) and a single Chinese Cancer Center (NCC cohort, n=268). Using a 1:2 ratio of propensity score matching (PSM), the prognostic impact of NAC for patients who underwent NAC before surgical treatment and patients who underwent surgical treatment alone was evaluated. Results After PSM, there was no significant difference in overall survival (OS) between patients receiving NAC prior to CRLM resection and those undergoing surgery only, in both the NCC and SEER cohorts (each P > 0.05). Age was an independent predictor of OS only in the SEER cohort (P = 0.040), while the pN stage was an independent predictor for OS only in the NCC cohort (P = 0.002). Furthermore, Disease-free survival (DFS) was comparable between the two groups in the NCC cohort. In a subgroup analysis, the DFS and OS in the NAC- group were significantly worse than those in the NAC+ group for patients with more than two liver metastases in the NCC cohort (P < 0.05 for both). Conclusion NAC did not have a significant prognostic impact in patients with resectable synchronous CRLM. However, patients with more than two liver metastases could be good candidates for receiving NAC.